Peningkatan Hasil Belajar Bangun Ruang menggunakan Media Permainan Jaring Bangun Ruang pada Siswa Kelas II SDN 1 Caringin - Elviani, Elsa; Rahayu, Delia Putri; Agustiani, Herlina; Berrae, Balandina; Hopeman, Teofilus Ardian (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
This research was conducted to identify the effect of using the spatial net game media on improving the learning outcomes of class II students at SDN 1 Caringin in the spatial mathematics subject. This type of research is classroom action research. The research approach used is a quantitative approach with an experimental pretest-post test control group design. The research subjects in the study were class II students at SDN 1 Caringin, totaling 27 students. The data collection methods used are documentation, observation and tests. The results of the research show that the use of spatial net game media significantly improves student learning outcomes in spatial construction material compared to conventional methods. Data collection techniques use tests. Based on the research results, it was concluded that the application of the game method could increase student learning outcomes from an average of 44% in the first cycle to 63%, while in the second cycle the average gain was. Based on the results of this research, it can be concluded that the building net game media is effectively used to improve the learning outcomes of class II students at SDN 1 Caringin in building space material. The use of this media can facilitate better understanding of concepts and increase student involvement in mathematics learning in elementary schools.